UMA ANÁLISE DAS POLÍTICAS INSTITUCIONAIS SOBRE REFUGIADOS NO ESTADO DO PARANÁ - OLIVEIRA, JULIANA MARQUES SANTOS (2023)
The refugee matter constitutes a very relevant social issue nowadays, since its reflexes within its context affect the reception and insertion process and the local reality. Brazil has taken an international commitment on hosting refugees when rectified and signed the 1951’ Convention and the 1967’ Protocol regarding the Statute of the Office of the United Nations High Commissioner for Refugees. Nevertheless the country counts with its own legislation on the matter through Lei 9.474/97, which is considered by UN as a parameter for other institutional policies in South America, so the continent has a similar jurisdiction. In the present research, we analyzed how the refugee matter is discussed and faced by Paraná State government and public policies, in order to obey the international and national protocol and guidelines on the refugees’ reception and insertion process, as well as the protection measures, applied according to the human dignity principle. Therefore, the methodology adopted relayed on the bibliographic and documental review, being characterized as exploratory research with quanti-qualitative perspective. The results show that the state of Paraná is developing and implementing actions regarding refugees, however they must be continuous and permanent, since matter is getting larger every day and it demands a bigger effort from public institutions so that the appropriated actions take place and be effective.